The Impact of a Community Supervision Officer Training Program on Client Outcomes: A Propensity Score Modeling Analysis by Officer Training Dosage - Labrecque, Ryan (Criminal justice and behavior, 2021)
A growing body of research indicates officer training in correctional supervision programs is associated with improved use of evidence-based practices and lower rates of client recidivism. This scholarship also suggests larger reductions in recidivism can be achieved when officers implement program skills with higher quality. Despite their potential, research has shown standard training regiments alone are not sufficient in making all participants proficient users of skills. There is a need to determine what intensity of training produces the best results. In response, this study assessed the impact of federal probation officer training dosage in the Staff Training Aimed at Reducing Re-arrest (STARR) program on the outcomes of their clients. The results indicated clients of STARR-trained officers had fewer probation revocations and new arrests but more technical violations and positive drug tests. We also found clients supervised by officers with more versus less exposure to the STARR model had better outcomes.